Triple Negative Breast Cancer is Dependent on the Lysosomal Cholesterol Transporter NPC1 - O’Neill, Kathleen (J Endocr Soc, 2021)
Background: Triple Negative Breast Cancer (TNBC) is an aggressive subtype of breast cancer (BC) with peak rate of metastasis within the first few years post diagnosis and few targeted therapies. Normal epithelial cells and estrogen receptor alpha (ER) positive BC express the microRNA-200c (miR-200c), a potent suppressor of epithelial-to-mesenchymal transition (EMT). However, miR-200c is silenced or lost in TNBC, allowing aberrant expression of genes conferring a de-differentiated, non-epithelial phenotype that confers invasive and chemo-resistant properties. Recent literature demonstrated that EMT also promotes altered tumor cell metabolism. Hypothesis: We postulate that EMT reversal in TNBC will reveal selective advantages and identify novel therapeutic vulnerabilities. Methods: We used restoration of miR-200c as a tool to identify selective advantages conferred by EMT. In addition to driving global metabolic changes, miR-200c-repressed key cholesterol metabolism genes that support the uptake of dietary cholesterol, which is delivered via low-density-lipoproteins (LDL) and processed by the lysosomal cholesterol transporter, Niemann-Pick Type C1 (NPC1). Manipulation of NPC1 by genetic and pharmacological means was used to determine if and how TNBC are reliant on this pathway. Results: We determined that NPC1 is overexpressed in TNBC relative to ER+BC (Nature Metabric P<0.0001). Restoration of miR-200c directly targets the NPC1 3’UTR and represses NPC1 by two-fold (p=0.01). While silencing of NPC1 in ER+ BC cells led to slowed proliferation, TNBC cell lines died within 48-72 hours. NPC1 is associated with mitochondrial dysfunction and mTOR suppression. Intracellular cholesterol homeostasis is critical for cell survival and is carefully regulated, but how these homeostatic mechanisms adapt during tumor progression is poorly understood. Conclusions: This study demonstrates that while mesenchymal-like TNBC cells do not require exogenous cholesterol from the microenvironment, this cancer type is sensitive to the loss of NPC1. Overall, this work identifies NPC1 as a novel target in TNBC and sheds light on how lysosomes and mitochondria interact to sense cholesterol and drive cell survival.